Conjugate Mirror by a Panda Ring Circuit - Preecha P. Yupapin (My University, 2013)
This paper presents the use of a nonlinear microring resonator device known as a modified add-drop filter for small scale conjugate mirror, which is a basic device for 3D image construction and reconstruction system. It can also be useful for real time 3D image display applications. By using the modified add-drop filter, the 3D image can be constructed and reconstructed within the microring circuit. In this circuit, the object and reference beams can be formed by the reflected signals from through and drop ports of the add-drop filter respectively, where the conjugate mirror concept is obtained by the nonlinear coupling effects via the two nonlinear side rings, in which the four-wave mixing of those signals can be introduced. Finally, the interference of those two beams can be constructed and seen by the whispering gallery mode at the center ring, while the interference signals can be seen by the add port output. The WGMs of waves are simulated and discussed, where the 3D image construction and reconstruction can be seen by using the microring circuit as the conjugate mirror, in which the use of large volume display using a new type of conjugate mirror can be realized.
Keywords: Conjugate; Pickup; Photonic and Optical Devices